2018
DOI: 10.3390/rs10020179
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Leaf Area Index in a Mountain Forest of Central Japan with a 30-m Spatial Resolution Based on Landsat Operational Land Imager Imagery: An Application of a Simple Model for Seasonal Monitoring

Abstract: An accurate estimation of the leaf area index (LAI) by satellite remote sensing is essential for studying the spatial variation of ecosystem structure. The goal of this study was to estimate the spatial variation of LAI over a forested catchment in a mountainous landscape (ca. 60 km 2 ) in central Japan.We used a simple model to estimate LAI using spectral reflectance by adapting the Monsi-Saeki light attenuation theory for satellite remote sensing. First, we applied the model to Landsat Operational Land Image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Indeed, the IAV of the d4PDF climate variables is lower than the average of the gridded climate data sets (Table S1), although they are usually not the lowest of all the data sets. The lower resolution of the BEAMS estimates compared with that of the in situ data may also contribute to the smaller GPP IAV because it flattens over large area with heterotrophic topography and vegetation (Melnikova et al, ). We assume all three of these factors contribute to the underestimation of GPP IAV by BEAMS compared with in situ observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the IAV of the d4PDF climate variables is lower than the average of the gridded climate data sets (Table S1), although they are usually not the lowest of all the data sets. The lower resolution of the BEAMS estimates compared with that of the in situ data may also contribute to the smaller GPP IAV because it flattens over large area with heterotrophic topography and vegetation (Melnikova et al, ). We assume all three of these factors contribute to the underestimation of GPP IAV by BEAMS compared with in situ observations.…”
Section: Resultsmentioning
confidence: 99%
“…Because LAI and FAPAR are related by the Beer–Lambert law according to the Monsi‐Saeki theory (Melnikova et al, ) and because not all of the satellite data sets provide FAPAR, we evaluated only the derived LAI by comparing it with several satellite data sets, as described in Table . In addition, we compared the estimated LAI with the LAI of prognostic models of the global 0.5° Model outputs of Multiscale Synthesis and Terrestrial Model Intercomparison Project (MsTMIP; Huntzinger et al, ) and the LAI of the Global Phenology Reanalysis (PhenoAnalysis) of Stöckli et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhikari et al examined the effect of C-Correction on fractional tree cover and found that ratio-based vegetation indices were not affected significantly [11]. Leaf Area Index model using Minnaert topographic correction has succeeded in improving the result, but this previous research did not compare the result to the uncorrected image [13]. Information regarding canopy density is important since the quality of vegetation stands can be figured out from this information; regardless, there is no change to the extent [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of remote sensing images is vulnerable to solar altitude, atmosphere conditions, and terrain-induced shadows, which lead to inaccuracies in spectral reflectance [14,15]. Due to terrain variation, the geometric relationships among the earth's surface, sensors, and solar illumination are not stable, thus the solar radiation received at different locations could be significantly different [16]. The areas with the same forest type and similar slopes but different aspects may have different spectral reflectance.…”
Section: Introductionmentioning
confidence: 99%